Combined effects of age and maturation on maximum isometric leg press strength in young basketball players - Ioakimidis, P.; Gerodimos, V.; Kellis, E.; Alexandris, N.; Kellis, S (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: Muscular strength of the leg extensor muscles in children can be affected by several factors such as age, sexual maturation, body mass and training status of the subjects. The purpose of the study was to examine maximal isometric strength characteristics of young male basketball players taking into consideration the combined effects of chronological age and sexual maturation. METHODS: One hundred and twenty male basketball players, aged from 12 to 17 years divided into 6 equivalent age subgroups performed maximum bilateral isometric leg press efforts. The parameters analysed were the maximal voluntary isometric force (MVC), relative strength (MVC/body mass and MVC/fat free mass), starting strength (F50: force exerted during the first 50 ms of the contraction) and speed strength index (the ratio of maximal force to time to attain maximal force). RESULTS: The results indicated that in almost all absolute force parameters, the 12-and 13-year olds demonstrated significantly (p<0.05) lower values compared with the 15(-1)6-and 17-years old groups. Age differences were also significant (p<0.05) when the effects of sexual maturation were taken into consideration in the statistical analysis but they were reduced when strength was adjusted for body mass. Finally, no significant differences for strength per unit of fat free mass were found (p>0.05). CONCLUSIONS: Maximum absolute strength of basketball players is significantly increased from 12 to 17 years and as sexual maturation stage increases. It also appears that body mass and fat free mass should be taken into consideration when examining age effects on strength in basketball players.